Controversies in the management of early endometrial carcinoma: an update - Rani, P. Reddi; Begum, Jasmina; Reddy, K. Sathyanarayana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Endometrial carcinoma (EC) is the commonest genital tract malignancy in developing countries and is usually confined to the uterus at the time of diagnosis with excellent prognosis and high cure rates. But the management is associated with lot of controversies like in staging, best surgical approach, extent of lymphadenectomy, adjuvant therapy, fertility sparing surgery in young women etc. A thorough surgical staging is important to determine uterine and extrauterine spread and also understanding of the pathophysiology and management strategies to identify women who are at high risk and tailoring the adjuvant treatment if necessary without increasing the morbidity. This evidence based narrative review conducted by searching Medline (1994- 2015) and other online articles from Pubmed, Google scholar. Articles were selected based on their currency and relevance to the discussion they summarize the current literature to provide an approach to best practice management of early endometrial carcinoma.